Characterizing computer-mediated communication, friendship, and social participation in adults with traumatic brain injury - Flynn, Margaret A. (Brain Inj, 2019)
BACKGROUND: Adults with traumatic brain injury (TBI) report loss of friendship and reduced social participation after injury, but there is limited information regarding quantity of friends and methods of communication. Our objective was to characterize friendship networks, social participation, and methods of communication, including computer-mediated communication (CMC), used by adults with TBI compared to uninjured adults. METHODS: Participants were 25 adults with TBI and 26 uninjured healthy comparisons (HC) adults, who completed the Participation Assessment with Recombined Tools-Objective (PART-O) and the Social Network Questionnaire (SNQ). RESULTS: Adults with TBI had significantly fewer total friends and significantly lower levels of productivity and overall social participation. Face-to-face interaction was the preferred method of contact for both groups. Adults with TBI were significantly less likely to use texting as a primary method of communication than their uninjured peers, but used other methods of communication at similar rates. CONCLUSION: Our study supports prior findings of reduced friendships and reduced social participation after TBI and adds new information about similarities and differences in communication methods between adults with and without TBI.